Novel Use of Household Items in Open and Robotic Surgical Skills Resident Education. (7th March 2019) - Rowley, Keri; Pruthi, Deepak; Al-Bayati, Osamah; Basler, Joseph; Liss, Michael A.
Abstract : Background . The aim of this study was to investigate the effectiveness of surgical simulators created using household items and to determine their potential role in surgical skills training. Methods . Ten urology residents attended a surgical skills workshop and practiced using surgical simulators and models. These included a wound closure model, an open prostatectomy model, a delicate tissue simulation, a knot-tying station, and a laparoscopic simulator. After the workshop, the residents completed a 5-point Likert questionnaire. Primary outcome was face validity of the models. Secondary outcomes included usefulness as a training tool and ability to replicate the models. Results . All models were easily created and successfully represented the surgical task being simulated. Residents evaluated the activities as being useful for training purposes overall. They also felt confident that they could recreate the simulators. Conclusion . Low-fidelity training models can be used to improve surgical skills at a reasonable cost. The models will require further evaluation to determine construct validity and to determine how the improvements translate to OR performance. While high-fidelity simulators may continue to be utilized in formal surgical training, residents should be encouraged to supplement their training with innovative homemade models.